Analysis of precise point positioning with GPS and glonass data in different latitudes - Jerez, Gabriel Oliveira [UNESP]; Vieira, João Vitor Espinhosa [UNESP]; Alves, Daniele Barroca Marra [UNESP] (Universidade Federal do Rio de Janeiro, 2020)
GNSS (Global Navigation Satellite System) is, nowadays, composed of two complete systems, GPS (Global Positioning System) and GLONASS (GLObal NAvigation Satellite System). Although the simultaneous development, the systems present different characteristics. Besides that, GLONASS passed through a degradation period, causing a lack in investigations related to the system. However, in 2011, GLONASS constellation was reestablished, this way, the interest in researches related to its performance was renewed. In this paper, we intended to investigate GPS and GLONASS performance in the autonomous and combined positioning, considering GNSS stations in different regions (latitudes), evaluating the positioning error, the amount of visible satellites and collected observables. In all the cases considered, the use of combined data led to better results. In 25% of the stations used, GLONASS presented better mean results than GPS, considering autonomous positioning.
Análise do posicionamento por ponto preciso com dados GPS e glonass em diferentes latitudes
Keywords: GLONASS; GNSS; GPS; Positioning; PPP